Teachers’ Strategies towards the Students’ Disruptive Behavior in Learning English - Reski Pilu; Purnama Cahya; Musfirah Musfirah (Universitas Cokroaminoto Palopo, 2019)
This research aims at finding out the students’ disruptive behaviors in learning English and the teachers’ strategies toward students’ disruptive behavior in learning English. The sample of this research 4 teachers. This research applied descriptive qualitative method. The instrument of this research is interview.Teacher uses many strategies such as, doing personal approach, displacing the students to sit in front, giving warning to the students and admonishing degree for the students who make disruptive in the class at the learning process.